A 100ks XMM-Newton view of the Seyfert 1.8 ESO113-G010. I. Discovery of large X-ray variability and study of the FeKalpha line complex - Porquet, D; Uttley, P; Reeves, J; Markowitz, A; Bianchi, S; Grosso, N; Miller, L; Deluit, S; George, I (2007)
(Abridged) We present here a long (100ks) XMM-Newton follow-up of the Seyfert 1.8 galaxy ESO113-G010 performed in November 2005, in order to study over a longer time-scale its main X-ray properties. The source was found in a higher/softer time-averaged flux state, and timing analysis of this source reveals strong, rapid variability. The Power Spectral Density (PSD) analysis indicates (at 95% c.l.) a break at 3.7 x 10^-4 Hz. This cut-off frequency is comparable to those measured in some other rapidly-variable Seyferts, such as MCG-6-30-15 and NGC4051. From the mass-luminosity-time-scale, we infer that M_BH ranges from 4 x 10^6 - 10^7 M_odot and the source is accreting at or close to the Eddington rate (or even higher). The existing data cannot distinguish between spectral pivoting of the continuum and a two-component origin for the spectral softening, primarily because the data do not span a broad enough flux range. In the case of the two-component model, the fractional offsets measured in the flux-flux plots increase significantly toward higher energies (similar to what is observed in MCG-6-30-15) as expected if there exists a constant reflection component. Contrary to May 2001, no significant highly redshifted emission line is observed (which might be related to the source flux level), while two narrow emission lines at about 6.5keV and 7keV are observed. The S/N is not high enough to establish if the lines are variable or constant. As already suggested by the 2001 observation, no significant constant narrow 6.4keV FeK line (EW~32eV) is observed, hence excluding any dominant emission from distant cold matter such as a torus in this Seyfert type 1.8 galaxy.